ERF-VII transcription factors induce ethanol fermentation in response to amino acid biosynthesis-inhibiting herbicides. (6th August 2019) - Gil-Monreal, Miriam; Giuntoli, Beatrice; Zabalza, Ana; Licausi, Francesco; Royuela, Mercedes
Abstract: Herbicides inhibiting either aromatic or branched-chain amino acid biosynthesis trigger similar physiological responses in plants, despite their different mechanism of action. Both types of herbicides are known to activate ethanol fermentation by inducing the expression of fermentative genes; however, the mechanism of such transcriptional regulation has not been investigated so far. In plants exposed to low-oxygen conditions, ethanol fermentation is transcriptionally controlled by the ethylene response factors-VII (ERF-VIIs), whose stability is controlled in an oxygen-dependent manner by the Cys-Arg branch of the N-degron pathway. In this study, we investigated the role of ERF-VIIs in the regulation of the ethanol fermentation pathway in herbicide-treated Arabidopsis plants grown under aerobic conditions. Our results demonstrate that these transcriptional regulators are stabilized in response to herbicide treatment and are required for ethanol fermentation in these conditions. We also observed that mutants with reduced fermentative potential exhibit higher sensitivity to herbicide treatments, thus revealing the existence of a mechanism that mimics oxygen deprivation to activate metabolic pathways that enhance herbicide tolerance. We speculate that this signaling pathway may represent a potential target in agriculture to affect tolerance to herbicides that inhibit amino acid biosynthesis. Abstract : ERF-VII transcription factors regulate the induction of ethanol fermentation upon amino acid biosynthesis-inhibiting herbicide treatment in plants grown with no oxygen limitations. A reduced fermentative potential enhances sensitivity to herbicides.